Referential Choice in the Written Narratives of Indonesian Adults - Katharina E. Sukamto (Badan Pengembangan dan Pembinaan Bahasa, 2020)
This study aims to describe the referential choice of two protagonist animate characters in a silent six-minute film entitled The Pear Story (Chafe, 1980). A total of 80 undergraduate and graduate Indonesian students were asked to watch the film and then retell the story by writing a narrative about the film in Indonesian. Findings indicate that when the protagonist animate referents are mentioned for the first time, a classifier seorang ‘a person’ is always used before the NP. When they are reactivated, they are mostly expressed by zero, pronouns dia or ia ‘he’, clitic –nya ‘his’ or ‘him’, NPs with determiners ini ‘this’, itu ‘that’, tersebut ‘aforementioned’, tadi ‘mentioned before’, NPs with relative clauses and NPs with definite articles si or sang ‘the’ which are often used in fables or tales. This study also demonstrates that the choice of anaphoric expressions of the protagonists is determined by factors such as referential distance and referential interference. This study confirms other cross-linguistic studies about referential choice – that there is a correlation between salience and referring expressions in discourse. AbstrakPenelitian ini bertujuan mendeskripsikan penggunaan acuan untuk dua tokoh utama dalam film bisu berdurasi enam menit yang berjudul The Pear Story (Chafe, 1980). Sebanyak 80 mahasiswa Indonesia tingkat Strata 1 dan Pascasarjana di sebuah universitas swasta diminta untuk menonton film tersebut dan kemudian menuliskan narasi mengenai film itu dalam bahasa Indonesia. Data menunjukkan bahwa jika referen kedua tokoh utama tersebut disebutkan untuk pertama kalinya, bentuk leksikal seorang selalu muncul sebelum frasa nomina (FN). Jika referennya diaktifkan kembali, maka yang digunakan adalah zero, pronomina dia atau ia, klitik –nya, FN + ini/itu/tersebut/tadi, FN + klausa relatif, dan si/sang + FN. Penelitian ini juga menunjukkan bahwa pilihan bentuk anaforik untuk kedua tokoh utama itu ditentukan oleh faktor jarak antara referen dan anteseden dan juga oleh adanya interferensi referen. Hasil penelitian ini sejalan dengan penelitian lintas bahasa mengenai pilihan acuan, yaitu bahwa ada korelasi antara referen utama dan bentuk acuannya.